Application of Intraoperative Ultrasound Navigation in Neurosurgery - Simfukwe, Keith; Iakimov, Iurii; Sufianov, Rinat; Borba, Luís; Mastronardi, Luciano; Shumadalova, Alina (Frontiers in Surgery, 2022)
Modern neurosurgery necessitates effective intraoperative image navigation techniques. In the last decade, intraoperative ultrasonography (iUS), a relatively inexpensive procedure, has gained widespread acceptance. Aim: To document and describe the neurosurgery cases in which iUS has been employed as the primary navigational tool. This includes a discussion of the advantages that iUS may possess relative to other forms of neuronavigation. Conclusion: The application of iUS as an intraoperative navigation tool during neurosurgery holds great potential as it has been shown, relative to other neuronavigation techniques, to be quick, repeatable, and able to provide real-time results.